The effect of mineral levels in the mother’s circulation on the outcome of pregnancy - Sudek, Hanan L.; Jaffer, Israa F.; Chyad, Zainab M. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Dietary intakes are critical during pregnancy, because inadequate amounts of key nutrients may compromise fetal development or maternal health. In addition to that maternal diet could be one of the methods to select the gender of the baby. The aim of the study is to correlate the level of the minerals in the mother’s blood with the gender and wellbeing of the baby after delivery. Patients and Methods: Fifty women were involved in this study with a mean age (23.92 ± 4.75), collected from the labor room during labor in the period between December 2013 and May 2014, in Baghdad teaching hospital. After taking a full history from the women, 10 ml of blood was withdrawn from them, 2ml in EDTA tubes for lead estimation and 8 ml in plain tubes, centrifuged and the serum was used for magnesium, copper, calcium and zinc estimation. The estimation was done by spectrophotometer method. Results: Birth weight of the delivered babies was correlated negatively but not significantly to the age of the delivered women. The level of the minerals in the maternal blood was not different between those who delivered male or female babies except for the zinc level which was higher in those women who give birth to male babies. The correlation between the birth weight of the babies and the level of maternal minerals shows a not significant positive correlation between them except for zinc which was significant and the lead level was correlated negatively but not significantly with birth weight. Conclusions: Age seems to have no significant effect on birth weight. There is no significant effect of the minerals level on the selection of the baby’s gender except for zinc which is higher in women with male babies, in addition to its significant effect on the birth weight being higher in women with higher birth weight babies.